The role of university-madrasah partnership in improving PGMI students’ career preparedness - Lesmana, Nadella; Firmansah, Deri; Negara, Hasan Sastra (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2025)
The career readiness of Madrasah Ibtidaiyah Teacher Education (PGMI) students is a crucial factor in shaping competent educators in the field of education. This study aims to explore the implementation of instructional strategies to enhance the career readiness of PGMI students. A qualitative research method with a case study approach was employed, involving two classes of sixth-semester PGMI students at a university. Data were collected through in-depth interviews, observations, and academic document analysis. The findings indicate that practice-based learning strategies, such as microteaching, field experience practice (PPL), and project-based learning, significantly impact students' pedagogical competencies. Additionally, the integration of technology in the learning process helps students develop digital skills relevant to modern educational demands. Challenges in implementing these strategies include limited practical facilities, students' readiness to apply theoretical knowledge to practice, and the lack of a structured career development program. This study concludes that the implementation of more practical and experience-based learning strategies can enhance PGMI students' career readiness. Therefore, it is recommended that educational institutions strengthen collaborations with madrasahs and other educational institutions and develop more intensive training programs for students.